PENGARUH KUALITAS PRODUK DAN BAGI HASIL TERHADAP KEPUTUSAN NASABAH DALAM MENABUNG PADA BANK MUAMALAT INDONESIA SYARIAH (Studi kasus pada Kantor Kas Baiturrahman Bank Muamalat Indonesia Syariah Semarang) - Hapsari, Trisera Renny; Waluyo, Handoyo Djoko; Widayanto, Widayanto (Jurnal Ilmu Administrasi Bisnis, 2015)
This study aimed to determine the effect of product quality and to save the results to the decision of Bank Muamalat Indonesia Indonesia Sharia. This type of research is explanatory. The number of samples taken were 100 respondents with accidental sampling method. Collecting data using questionnaires, interviews, observation. Testing hypotheses using statistical analysis covering the correlation coefficient, coefficient of determination, t-test and F test results of this study show that in partial positive influence on product quality saving decisions by 17.7%, the variable for the result a positive effect on saving decisions by 4.7%. Simultaneously, the variable quality of the product and the results of a positive influence on the decision of saving of 22.4%.